The Performance of Local Governments in Kaligandaki Rural Municipality of Syangja District, Nepal: An Assessment - Dahal, Girdhari (Journal of Political Science, 2024)
Since the establishment of the Federal Democratic Republic of Nepal, the Constitution of Nepal 2015 has given the local governments a great deal of power and authority. Consequently, a lot of changes have been noticed in most of the local levels. The present study is about the performance level of local government of Kaligandaki Rural Municipality of Syangja District in Gandaki Province, Nepal. The main issues and objectives that encouraged this study are to identify the types of achievement the local government has made during its tenure from 2017 to 2022, and to explain how it has accomplished the performance. The government has carried out different development activities related to public goodness in the study area. The activities related to passing and enacting laws, and improving education, drinking water, health care, insurance, farming, roads, irrigation, job opportunities and people’s increased participation in decision-making level have been successfully implemented. The study demonstrates that the local leaders of this municipality have accomplished their tasks among the grassroots by encompassing inclusive development models. The findings of the study conclude that besides exercising democratic practice and democratic institutionalization, the local government has displays high level of performance regarding local development in this rural municipality, and this performance indicates the significance of empowering local levels in Nepal.